India and the Indianness of Christianity: essays on understanding, historical, theological, and bibliographical, in honor of Robert Eric Frykenberg - Young, Richard Fox (Studies in the history of Christian missions, 2009)
Indian participation in enabling, sustaining, and promoting Christian mission in India / Daniel Jeyaraj -- "Ancient churches" and modern missions in the nineteenth century / Wilbert R. Shenk -- Empire and misinformation : Christianity and colonial knowledge from a South Indian Hindu perspective (ca. 1804) / Richard Fox Young -- Creating Christian community in early-nineteenth-century Agra / Avril A. Powell -- An "ardour" of devotion : the spiritual legacy of Henry Martyn / Brian Stanley -- Revival, syncretism, and the anticolonial discourse of the Kherwar movement, 1871-1910 / Peter B. Andersen -- Caste, Catholicism, and history "from below," 1863-1917 / Chandra Mallampalli -- Hindu pundits and missionary "knowledge" of Hinduism / Geoffrey A. Oddie -- Proselytism in the history of Christianity in India / Michael Bergunder -- Anticipating independent India : the idea of the Lutheran Christian nation and Indian nationalism / Gunnel Cederlöf -- Indian Christians and Nehru's nation-state / Judith M. Brown -- Christian interpretation of "Hinduism" : between understanding and theological judgment / John B. Carman -- An overview and analysis of missionary collections in the United Kingdom relating to South Asia / Rosemary Seton -- North American sources for the study of Protestant Christian missions in India / Martha Lund Smalley